PENDEKATAN ILMU FISIKA DAN MATEMATIKA DALAM MEMAHAMI KONSEP REAKSI OKSIDASI- REDUKSI (REDOKS) - Bukhari Bukhari (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Chemistry is one part of the Natural Sciences that explains the process of taking a reaction. In understanding the process of such reactions is needed knowledge of basic science of others such as Science Physics, Biology, and Mathematics. One of the materials taught in Chemistry is the Reduction and Oxidation reaction (redox). To facilitate an understanding of the concept of redox reactions it is advisable to first understand the Basic Mathematics and Physics Sciences, as most of the redox reactions are solved by mathematical concepts and Physics concepts. The calculations that exist in redox reactions are easily solved by the concept of Mathematical Sciences while the completion of the load must be by the Science of Physics. There are three methods or ways to complete the redox reactions, namely the method of capture and release of oxygen, the method of electron change and the method of heating the oxidation number.